Chromosome‐level genome assembly of the greenfin horse‐faced filefish (Thamnaconus septentrionalis) using Oxford Nanopore PromethION sequencing and Hi‐C technology. (9th July 2020) - Bian, Li; Li, Fenghui; Ge, Jianlong; Wang, Pengfei; Chang, Qing; Zhang, Shengnong; Li, Jie; Liu, Changlin; Liu, Kun; Liu, Xintian; Li, Xuming; Chen, Hongju; et al.
Abstract: The greenfin horse‐faced filefish, Thamnaconus septentrionalis, is a valuable commercial fish species that is widely distributed in the Indo‐West Pacific Ocean. This fish has characteristic blue–green fins, rough skin and a spine‐like first dorsal fin. Thamnaconus septentrionalis is of conservation concern because its population has declined sharply, and it is an important marine aquaculture fish species in China. Genomic resources for the filefish are lacking, and no reference genome has been released. In this study, the first chromosome‐level genome of T. septentrionalis was constructed using nanopore sequencing and Hi‐C technology. A total of 50.95 Gb polished nanopore sequences were generated and were assembled into a 474.31‐Mb genome, accounting for 96.45% of the estimated genome size of this filefish. The assembled genome contained only 242 contigs, and the achieved contig N50 was 22.46 Mb, a surprisingly high value among all sequenced fish species. Hi‐C scaffolding of the genome resulted in 20 pseudochromosomes containing 99.44% of the total assembled sequences. The genome contained 67.35 Mb of repeat sequences, accounting for 14.2% of the assembly. A total of 22, 067 protein‐coding genes were predicted, 94.82% of which were successfully annotated with putative functions. Furthermore, a phylogenetic tree was constructed using 1, 872 single‐copy orthologous genes, and 67 unique gene families were identified in the filefish genome. This high‐quality assembled genome will be a valuable resource for a range of future genomic, conservation and breeding studies of T. septentrionalis .